Isolated intracranial fibromuscular dysplasia presents as stroke in a 19-year-old female Diplasia fibromuscular intracraniana isolada manifestando-se como acidente vascular cerebral em mulher de 19 anos - Lee A. Birnbaum; Richard Sherry; Edgard Pereira (Arquivos de Neuro-Psiquiatria)
Isolated intracranial fibromuscular dysplasia is rare and may present with cerebrovascular events. It should be considered as etiology of stroke in otherwise healthy young patients. Though diagnosis is often challenging, characteristic morphologies may be revealed on magnetic resonance and catheter angiography. Cephalocervical fibromuscular dysplasia typically involves the extracranial portion of the internal carotid artery (nearly 95%). This rare case demonstrates isolated intracranial fibromuscular dysplasia in a 19-year-old female with left caudate and genu of internal capsule stroke. Displasia fibromuscular intracraniana isolada é rara e pode se apresentar como acidente vascular cerebral (AVC). Ela deve ser considerada como etiologia do AVC em paciente jovem saudável. Embora o seu diagnóstico possa ser um desafio, características morfológicas específicas podem ser reveladas através da angiografia através de ressonância nuclear magnética e por de catéter. A displasia fibromuscular envolvendo a circulação cérvico-cefálica afeta tipicamente a artéria carótida interna extracraniana (95%). O presente caso relata uma rara ocorrência de displasia fibromuscular intracraniana em uma jovem de 19 anos com infarto do núcleo caudado e joelho da cápsula interna à esquerda.